Chemotherapy for Metastatic Invasive Intraductal Papillary Mucinous Neoplasms (IPMNs) of the Pancreas - Lucchesi, Maurizio; Vasile, Enrico; Caponi, Sara; Ginocchi, Laura; Caparello, Chiara; Falcone, Alfredo (JOP. Journal of the Pancreas, 2012)
Context IPMNs are intraductal mucin-producing cystic neoplasms of the pancreas. The incidence of these neoplasms is rising and it has been reported in recent works that IPMNs account for approximately 25% of resected pancreatic neoplasms. It has been described that recurrence of disease is observed in 26-65% of patients resected for invasive IPMN (also named papillary mucinous carcinoma), usually within 3 years from surgery and often in form of distant disease. The natural history of metastatic invasive IPMNs is not clear and few data regarding the role of palliative treatments are available. Objective To evaluate the clinical outcome of this disease and the response to medical treatment. Methods We retrospectively collected data about patients with diagnosis of metastatic invasive IPMN who were treated with palliative chemotherapy at our institution from 2008 to 2012. Results Thirteen patients (M/F 8/5) affected by metastatic invasive IPMN were identified. Median age was 69 years (range 64-81). Most patients (12, 92%) had a recurrence after radical resection while one patient had synchronous metastases. All patients were treated with first line gemcitabine-based chemotherapy: seven (54%) patients received gemcitabine monotherapy; six (46%) received the combination of gemcitabine and oxaliplatin. All patients except one experienced disease progression and 6 died. Two (15%) patients experienced partial response with first-line chemotherapy; 6 (46%) had stable disease while 5 (38%) showed disease progression. The estimated median progression-free survival was 9.6 months. Eight patient received also further lines of chemotherapy. Median overall survival was 15.4 months. Conclusion Our results confirm that metastatic invasive IPMNs have a dismal prognosis. The outcome of these patients is similar to patients affected by pancreatic ductal adenocarcinoma. In the absence of prospective clinical trials conducted in patients with this histology, the choice of chemotherapy should be based on data about pancreatic ductal adenocarcinoma.